Low cost polytanks for higher water productivity in hills - KUMARI, Utkarsh; Kumar, Jitendra; Singh, Sher; Parihar, Manoj (Indian Farming, 2020)
Agriculture is the main source of livelihood for the the North Western Himalayan (NWH) farmers who predominantly, being marginal farmers, pursue rain-dependent agriculture and face serious water-related constraints. Therefore, an efficient technique for conservation and scientific management of harvested water is essential for the profitable crop production especially for highvalue crops like fruits and vegetables. The hilly soils are light in texture which results in higher seepage and percolation losses which renders construction of Kaccha pond, a non-feasible option for runoff conservation. In such a situation, low cost poly-tank can be a useful strategy to harvest the rain water in hilly region. This article describes the successful implementation of low cost poly-tank (LCP) in agri-horti system in higher hills of Uttarakhand.